The role of physical condition in the smash skills of guidance achievement badminton athletes - Novriady Novriady; Nurul Ihsan; Umar Umar; Ahmad Chaeroni; Andri Gemaini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study examines the direct and indirect effects of arm muscle explosive power, hand-eye coordination, and flexibility on smash ability among badminton players at PB Cahaya Pinang. Using a quantitative approach with path analysis, 14 male athletes were selected as participants. Data was collected through sport-specific tests: the two-hand medicine ball throw for explosive power, a tennis ball throw-and-catch test for hand-eye coordination, shoulder and wrist flexibility tests, and a smash performance test. The results revealed that flexibility had the strongest direct effect on smash ability (p = 0.906), followed by arm muscle explosive power (p = 0.270) and hand-eye coordination (p = 0.264). Flexibility also mediated the effects of arm muscle explosive power (64.4%) and hand-eye coordination (40.8%). Together, these variables accounted for 96.4% of the variance in smash ability, highlighting the integrated role of physical components in badminton performance.